Konsep Dasar Inovasi Pendidikan Dan Pembelajaran Pendidikan Agama Islam - Asy'arie, Bima Fandi (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
One very important component in the formation of generations is Islamic religious education (PAI). This research is a literature study with a qualitative approach. This research aims to understand the basic concepts of PAI education and learning innovation. The Qur'an, al-Hadith, philosophy, history, psychology, sociologist, scientific, and technological education are the pillars or foundations of education. Nurturing human beings intellectually, emotionally, and spiritually is the main goal of education. Educational principles are frameworks that include information about the quality of learning materials that have been informally evaluated as guidelines. The four principles that must exist in education are humanism, humanization, humanities, and humanity. PAI learning is one of the subjects taught in schools, madrasahs, and pesantren. PAI teachers can use basic learning strategies such as determining the beginning of learning, mastering the material, choosing media methods and models, and assessing learning outcomes.